A novel missense mutation of GJA8 causes congenital cataract in a large Mauritanian family. Issue 6 (November 2019) - Hadrami, Mouna; Bonnet, Crystel; Veten, Fatimetou; Zeitz, Christina; Condroyer, Christel; Wang, Panfeng; Biya, Mohamed; Sidi Ahmed, Med Ahmed; Zhang, Qingjiong; Cheikh, Sidi; Audo, Isabelle; Petit, Christine; et al.
Objective of the study: Inborn lens opacity is the most frequent cause of childhood blindness. In this study, we aimed to define the presumed genetic cause of a congenital cataract present in a Mauritanian family over the last nine generations. Methods: A family history of the disease and eye examination were carried out for the family members. Next-generation sequencing using a panel of 116 cataract underlying genes was selectively conducted on the proband's DNA. Nucleotide and amino acid changes and their impact on the phenotype were evaluated using various data analyzing software. Results: Congenital nuclear cataract, with autosomal dominant mode, was observed in the family. All patients had consequences on their vision in the first 2 years of life. Genetic screening revealed a new mutation c.166A>C (p.Thr56Pro) in GJA8, encoding the Cx50 α-connexin protein. This mutation co-segregated in all patients and was not observed in the unaffected family members and controls. The predicted secondary structure impacted by p.Thr56Pro revealed a localized disruption, in the first extra membrane loop of the wild-type sheet, which is replaced in the mutant protein by a turn then a coil. This conformational change was functionally predicted as probably damaging. Conclusion: A new mutation (c.166A>C) in GJA8 underlying a nuclear congenital cataract was identified in this study. Its segregation with the phenotype might be useful as a predicting marker of the disease.